Australian trachoma surveillance annual report, 2013 - Cowling, C.; Liu, B.; Snelling, Thomas; Ward, J.; Kaldor, J.; Wilson, D. (2016)
Australia remains the only developed country to have endemic levels of trachoma (a prevalence of 5% or greater among children) in some regions. Endemic trachoma in Australia is found predominantly in remote and very remote Aboriginal communities. The Australian Government funds the National Trachoma Surveillance and Reporting Unit to collate, analyse and report trachoma prevalence data and document trachoma control strategies in Australia through an annual surveillance report. This report presents data collected in 2013. Data are collected from Aboriginal and Torres Strait Island communities designated at-risk for endemic trachoma within New South Wales, the Northern Territory, South Australia and Western Australia. The World Health Organization grading criteria were used to diagnose cases of trachoma in Aboriginal children, with jurisdictions focusing screening activities on the 5-9 years age group; but some children in the 1-4 and 10-14 years age groups were also screened. The prevalence of trachoma within a community was used to guide treatment strategies as a public health response. Aboriginal adults aged 40 years or over were screened for trichiasis. Screening coverage for the estimated population of children aged 5-9 years and adults aged 40 years or over in at-risk communities required to be screened in 2013 was 84% and 30%, respectively. There was a 4% prevalence of trachoma among children aged 5-9 years who were screened. Of communities screened, 50% were found to have no cases of active trachoma and 33% were found to have endemic levels of trachoma. Treatment was required in 75 at-risk communities screened. Treatment coverage for active cases and their contacts varied between jurisdictions from 79% to 100%. Trichiasis prevalence was 1% within the screened communities.